Relationship of Parity and Age with Post Delivery Primary Blooding - Eni Monaliska Sihombing (Pena Cendekia Insani, 2022)
Effort enhancement health is something activity or series activities carried out for maintain and increase degrees health especially to mother and child. height number dead mother and child caused the influence is high parity and age mother pregnancy that results in many risk to childbirth. Destination study this is For knowing connection parity and age with incident post primary haemorrhage labor in the region work Public health center Cape Morawa . Type study this is analytic with approach cross sectional. Amount population on study this is whole mother maternity in April-July in Public health center Cape Morawa as many as 31 people . With taking sample use technique total population that is whole population made sample. Test used is use test Chi-square. Tool data collection on study this with use questionnaire. From result study connection Among parity with post primary haemorrhage labor obtained results chisquare i.e. 0.017 < 0.05 where 0.017 is more small from 0.05 which states there is connection Among second variable, and connection Among age with incident post primary haemorrhage labor obtained results chisquare i.e. 0.000 < 0.05 where p<0.001 is more small from 0.05 which states there is connection Among second variable. Conclusion on results study this is that there is connection parity with incident post primary haemorrhage childbirth, and there is connection age with incident post primary haemorrhage labor in accordance with results chisquare, so that could recommended to power health for more often to do counseling sign danger pregnancy for mother could increase understanding about sign danger During time pregnancy and labor consequence influence parity and age.